Commercial Code, he should be or not to be? Part 2 - Юлдашев Сергей Aлексеевич (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The problems associated with the adoption and operation of the Commercial Code of Ukraine, the dualism in the legal regulation of property relations. The history of the emergence of the economic rights, one of the possible methodological approaches to improving the legal regulation of economic activity, solving the problem of inconsistency of the Commercial Code, the Civil and the direction of the first decision on the main actual problems of the economy.